Dual-Band, EBG-DGS Wearable Antenna for Emergency Services and Responses in WBAN - Mallavarapu, Sandhya; Lokam, Anjaneyulu (Electrical, Control and Communication Engineering, 2022)
The paper introduces a compact, thin flexible textile antenna integrated with an Electromagnetic Bandgap (EBG) and Defected Ground Structure (DGS) covering the Wireless Local Area Networks (WLAN) bands (2.4-2.485 GHz and 5.1-5.9 GHz) for emergency services and responses. The geometry and configuration of the proposed antenna are made from common clothing jeans fabric, which makes the antenna more flexible, thin, and conformal. A new configuration of EBG structure is developed using Minkowski fractal geometry as base geometry and a DGS with the complementary dumbbell-shaped slot to operate in WLAN standards. The EBG structure is used to isolate the antenna from the human body, whereas the DGS is used to improve the bandwidth and polarization purity. The prototype covers the WLAN bands with gains of 3.37 dBi and 6.47 dBi, a bandwidth of 115.9 MHz, and 398.06 MHz for the specified wireless bands. The integrated antenna demonstrates a Front to Back Ratio (FBR) of 16.77 dB and 32.72 dB, the radiation efficiency of 36.9 % and 73.8 %, and a better cross-polarization level at 2.45 GHz, 5.85 GHz, respectively. The antenna shows a high gain and an efficiency of about 70 % under the various bending scenario. Thus, the anticipated antenna is the most appropriate and potential candidate for wearable applications in various domains.